2021
DOI: 10.1126/scitranslmed.abd6434
|View full text |Cite
|
Sign up to set email alerts
|

The melanocortin-3 receptor is a pharmacological target for the regulation of anorexia

Abstract: Ablation of hypothalamic AgRP (Agouti-related protein) neurons is known to lead to fatal anorexia, whereas their activation stimulates voracious feeding and suppresses other motivational states including fear and anxiety. Despite the critical role of AgRP neurons in bidirectionally controlling feeding, there are currently no therapeutics available specifically targeting this circuitry. The melanocortin-3 receptor (MC3R) is expressed in multiple brain regions and exhibits sexual dimorphism of expression in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 52 publications
1
55
2
Order By: Relevance
“…In contrast, our homozygous null proband has been obese since early childhood, with no evidence for mutations in known obesity genes. MC3R is expressed on both POMC and AgRP neurons and could influence their function in controlling energy balance 39 . Resolution of this question will require the identification of additional humans homozygous for LoF MC3R mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our homozygous null proband has been obese since early childhood, with no evidence for mutations in known obesity genes. MC3R is expressed on both POMC and AgRP neurons and could influence their function in controlling energy balance 39 . Resolution of this question will require the identification of additional humans homozygous for LoF MC3R mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Using a single-cell RNA sequencing dataset of the arcuate nucleus (ARC) 38 Sweeney et al 39 recently reported that Mc3r expression was significantly enriched in neurons expressing Kisspeptin, Neurokinin B and Dynorphin (so called KNDy neurons) and in Growth Hormone-releasing Hormone (GHRH) neurons. We undertook an expanded analysis including three additional studies [40][41][42] S12).…”
Section: Mc3r Expression In the Hypothalamusmentioning
confidence: 99%
“…POMC is posttranslationally cleaved by proconvertases (PC1 and PC2) and other peptidases to create several smaller peptides including β-endorphin and α-melanocyte stimulating hormone (α-MSH) (Benjannet et al, 1991). α-MSH inhibits energy intake and stimulates energy expenditure via melanocortin 4 receptors (MC4R) and, to a lesser degree, melanocortin 3 receptors (MC3R) located on second order neurons (Seeley et al, 1997;Sweeney et al, 2021). AgRP is an antagonist of MC4R (Ollmann et al, 1997) and opposes the effects of POMC.…”
Section: The Intrauterine Environmentmentioning
confidence: 99%
“…We elected to use male mice because it is well established that male C57BL/6J mice are much more susceptible than females to dyslipidaemia, weight gain and glucose intolerance in response to high-fat diets [ 46 , 54 , 55 , 56 ]. Furthermore, the magnitude of knockout genotype effects in females in metabolic phenotyping studies is often much lower than in their male counterparts [ 57 , 58 , 59 , 60 ]. If a scientifically or clinically valuable phenotype had emerged in this study, follow-up experiments with female mice would be justified.…”
Section: Discussionmentioning
confidence: 99%